The Implementation of Repentance, Confession, and Penance in the Sacrament of Reconciliation at Stasi Santo Thomas Onan Rihit - Fajariyanto, Tri Chandra; Sihombing, Melisa Febriani (Prodi Studi Agama-Agama, 2024)
The Sacrament of Reconciliation, central to Catholic doctrine, facilitates the restoration of relationships between the penitent, the community, and the divine. This study examines the implementation and experiences of the sacrament through the essential acts of repentance, confession, and penance, highlighting their roles in spiritual and moral transformations. Employing a qualitative approach, the research gathered data through observations, in-depth interviews, and documentation at Stasi Santo Thomas Rasul Onan Rihit. The findings reveal that repentance initiates spiritual renewal while confession promotes transparency and humility, thereby strengthening communal bonds. Penance, tailored to individual transgressions, not only addresses past wrongs but also fosters spiritual growth and community harmony. Challenges remain in fully engaging penitents with the sacrament, pointing to the need for enhanced pastoral support and theological education. This study underscores the sacrament's enduring relevance and its capacity to facilitate profound spiritual life within the contemporary Catholic context.